The Bourne legacy [videorecording (DVD)] - Gilroy, Tony; Gilroy, Tony; Gilroy, Dan, 1959-; Marshall, Frank; Crowley, Patrick Timothy; Smith, Ben Burden; Weiner, Jeffrey M.; Renner, Jeremy; Glenn, Scott, 1942-; Weisz, Rachel, 1970-; Allen, Joan, 1956-; Keach, Stacy; et al. (Universal, 2016)
Aaron Cross is an agent groomed by the government program that also unleashed Jason Bourne, but with a few new wrinkles. Cross is busy training in Alaska when he's caught in a tsunami of hurt, thus beginning a frantic search for answers to who and what he is.